2017
DOI: 10.1002/ejoc.201700920
|View full text |Cite
|
Sign up to set email alerts
|

The Baldwin Rearrangement: Synthesis of 2‐Acylaziridines

Abstract: International audienc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 100 publications
(68 reference statements)
0
16
0
1
Order By: Relevance
“…Subsequent reductive eliminationo fP hI yields iminoisoxazoline C or isothiazoline 4a. Due to the instability of the NÀObond under the reactionconditions, intermediate C undergoes further Baldwin rearrangement [23] to afford oxazoline 2a through olefinic C=Cb ond cleavage/cyclization of the iminoacyl-aziridine species D.T he formation of isothiazoline has suggested that the NÀSb ond in 4a is stable under the stated conditions, whereas the NÀO bond in isoxazoline C cannotwithstand the reactionconditions and thus undergoes further NÀOc leavager eaction to form oxazoline 2a.…”
mentioning
confidence: 99%
“…Subsequent reductive eliminationo fP hI yields iminoisoxazoline C or isothiazoline 4a. Due to the instability of the NÀObond under the reactionconditions, intermediate C undergoes further Baldwin rearrangement [23] to afford oxazoline 2a through olefinic C=Cb ond cleavage/cyclization of the iminoacyl-aziridine species D.T he formation of isothiazoline has suggested that the NÀSb ond in 4a is stable under the stated conditions, whereas the NÀO bond in isoxazoline C cannotwithstand the reactionconditions and thus undergoes further NÀOc leavager eaction to form oxazoline 2a.…”
mentioning
confidence: 99%
“…The initial strategy was revised; functional group manipulations of 1.7 furnished nitrone 1.8 , which was primed for a [3+2] cycloaddition. Heating 1.8 in toluene gave aziridine 1.10 , presumably obtained via an unexpected Baldwin rearrangement of 1.9 [9c] . Nishikawa surmised 1.10 might be useful if the correct C3 stereochemistry was present, though the origins of the stereoselectivity were not remarked upon.…”
Section: Syntheses Of the Core Of Pactamycinmentioning
confidence: 99%
“…Die Anfangsstrategie wurde dahingehend überarbeitet, dass durch Modifikationen funktioneller Gruppen von 1.7 das Nitron 1.8 erzeugt wurde, das für eine [3+2]‐Cycloaddition geeignet war. Durch Erhitzen von 1.8 in Toluol wurde das Aziridin 1.10 erhalten, das vermutlich über eine unerwartete Baldwin‐Umlagerung von 1.9 entstand [9c] . Nishikawa vermutete, dass 1.10 verwendet werden könnte, falls die richtige C3‐Konfiguration vorlag, wenngleich nichts über die Stereoselektivität angemerkt wurde.…”
Section: Synthesen Des Kerns Von Pactamycinunclassified